Future treatments for the arteriopathy of ectopic calcification disorders - Davies, Benjamin M.; Rutsch, Frank; Vyavahare, Naren; Jones, Alexander (Frontiers in Drug Discovery, 2023)
Ectopic calcification disorders, including Generalized Arterial Calcification of Infancy (GACI) and Pseudoxanthoma Elasticum are rare but impactful on individuals, healthcare and society, with significant associated morbidity, mortality and healthcare costs (Terry and Uitto, 2020; Ziegler et al., 2020). Available therapies are not curative and focus on reducing extracellular calcification to limit progression of the arteriopathy that is responsible for much of the morbidity and, in the case of GACI, significant early mortality (approximately 50% in infancy) (Kawai et al., 2022). In this article, current and emerging medical approaches are reviewed and critiqued, including dietary manipulation, phosphate binders, bisphosphonates, tissue nonspecific alkaline phosphatase inhibitors, ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) enzyme replacement, allele-specific therapies, gene therapies, and antibody targeted treatment. Available therapies may limit further arterial calcification, but in GACI in particular, significant calcification can be present at birth, contributing to high infant mortality. This highlights the need for new approaches that aim to reverse established calcification, rather than merely slow its progression. Recently, a promising new class of antibody-targeted nanoparticle therapeutics has emerged that can reverse established arterial calcification in animals, restoring arterial elasticity. In one realization, nanoparticles carry established chelators, such as ethylenediaminetetraacetic disodium acid, to sites of arterial damage, concentrating the impact of the chelator where it is needed and limiting off-target effects. Such drugs would complement existing and emerging therapies, such as ENPP1 enzyme replacement, that slow or prevent progression of calcification, by offering an opportunity to “reset” arterial health in ectopic calcification disorders. At present, ectopic calcification disorders are challenging to treat effectively and carry a high burden of morbidity and mortality, particularly in GACI. Recent drug developments offer good reason to be hopeful for a new era of effective therapeutics that may reverse established arterial disease as well as halt its progression.